2019
DOI: 10.5937/gp23-20463
|View full text |Cite
|
Sign up to set email alerts
|

Karst geoheritage and geotourism potential in the Pek River lower basin (eastern Serbia)

Abstract: Karst areas, as areas with attractive geological and geomorphological features are an important and integral part of geoheritage. They possess huge tourism potential and can be used for the development of geotourism. The Pek River basin is a highly dominant karst terrain with numerous geological and geomorphological features, especially caves. However, their geotourism potential still remains fully unrevealed. In this paper, we analyzed several geosites that represent significant karst geoheritage formations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 27 publications
(33 reference statements)
1
20
0
1
Order By: Relevance
“…Geoheritage and geosite studies have assumed growing scientific importance in the past 25 years, and territorial legislative initiatives have emerged all around the world. Geoheritage studies have usually been carried out in terrestrial environments: Mountain areas (e.g., [1][2][3][4][5][6]), coastal areas (e.g., [7][8][9][10][11]), karst areas (e.g., [12][13][14][15][16]), fluvial areas (e.g., [17][18][19]), and volcanic areas ( [20][21][22][23]). Recently, a great deal of interest has concerned also geoheritage in urban areas (e.g., [24][25][26][27][28][29][30]).…”
Section: Introductionmentioning
confidence: 99%
“…Geoheritage and geosite studies have assumed growing scientific importance in the past 25 years, and territorial legislative initiatives have emerged all around the world. Geoheritage studies have usually been carried out in terrestrial environments: Mountain areas (e.g., [1][2][3][4][5][6]), coastal areas (e.g., [7][8][9][10][11]), karst areas (e.g., [12][13][14][15][16]), fluvial areas (e.g., [17][18][19]), and volcanic areas ( [20][21][22][23]). Recently, a great deal of interest has concerned also geoheritage in urban areas (e.g., [24][25][26][27][28][29][30]).…”
Section: Introductionmentioning
confidence: 99%
“…The first is the Geosite Assessment Model (GAM) scientifically based for geolocation evaluation purposes. The model was created by Vujičić et al [54] based on a numerous scientific works in the field of evaluation [46,[67][68][69][70][71][72][73][74][75] and it was scientifically established later on [49,60,76]. This method evaluated the subindicators, on the basis of which the assessment of the geo-tourist values of the mine was determined.…”
Section: Methodsmentioning
confidence: 99%
“…The main objectives of geotourism include promotion and protection of geoheritage throughout tourism activities along with educational and interpretive elements in order to increase the awareness of the wider public for conservation needs as well as sustainable development of the tourism industry [49,50].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Encompassing all the knowledge about the importance of cave management and other geosites, there is an urgent need to approach speleotourism in Serbia strategically in order to gain greater importance in the tourism market. Studies on speleotourism in Serbia (Petrović, 2006;Antić, 2018;Antić et al, 2019;Tomić et al, 2019;Vuković & Antić, 2019) have shown that caves possess an extraordinary tourism potential, which can have an exceptional impact on tourism development at a national level.…”
Section: Introductionmentioning
confidence: 99%